Student Concept Mastery on Coloid Material Through Radec Learning - Rukiyahtul Adawiyah Ritonga; Wahyu Sopandi; Momo Rosbiono (Universitas Riau, 2021)
Mastery of concepts is still the main standard of learning success in Indonesia. This study aims to analyze students' conceptual mastery of colloidal material through the RADEC (Read, Answer, Discuss, Explain, and Create) learning model. The research method used is the Pre-Experiment method with the research design of One Group Pretest-Posttest Design. The number of subjects in this study were 18 students. Data were collected using 25 multiple choice items used for pretest and posttest. Data were analyzed through normality test, t test and N-gain using SPSS version 21 for windows. The results of the Paired Sample T-Test showed that there was a significant difference between the pretest score (39.7) and posttest score (74.4) (p<0.05) with the N-gain value obtained was 0.56. This means that there is an increase in the medium category in students' concept mastery through RADEC learning.